2015
DOI: 10.1038/boneres.2014.50
|View full text |Cite
|
Sign up to set email alerts
|

Contaminated open fracture and crush injury: a murine model

Abstract: Modern warfare has caused a large number of severe extremity injuries, many of which become infected. In more recent conflicts, a pattern of co-infection with Acinetobacter baumannii and methicillin-resistant Staphylococcus aureus has emerged. We attempted to recreate this pattern in an animal model to evaluate the role of vascularity in contaminated open fractures. Historically, it has been observed that infected bones frequently appear hypovascular, but vascularity in association with bone infection has not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The establishment of a functional vascularization represents one of the major challenges to be overcome for the broad implementation of tissue engineering applications into clinical practice. This neovascularization occurs through a series of steps, including stimulation of endothelial cells (ECs) by autocrine and paracrine growth factors, proteolytic degradation of the basement membrane and surrounding extracellular matrix, ECs proliferation and migration, and structural reorganization into a three‐dimensionally tubular structure …”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The establishment of a functional vascularization represents one of the major challenges to be overcome for the broad implementation of tissue engineering applications into clinical practice. This neovascularization occurs through a series of steps, including stimulation of endothelial cells (ECs) by autocrine and paracrine growth factors, proteolytic degradation of the basement membrane and surrounding extracellular matrix, ECs proliferation and migration, and structural reorganization into a three‐dimensionally tubular structure …”
Section: Introductionmentioning
confidence: 98%
“…growth factors, proteolytic degradation of the basement membrane and surrounding extracellular matrix, ECs proliferation and migration, 1 and structural reorganization into a three-dimensionally tubular structure. 2 Recent studies focused on angiogenesis has been elucidated that adipose-derived stromal cells (ASCs) have a great potential in vascular regeneration. ASCs can promote endothelial tubulogenesis and eventually promote neovascularization or angiogenesis by secreting angiogenic cytokines and growth factors in a paracrine manner.…”
mentioning
confidence: 99%
“…Angiogenesis is an intricate process involving the activation of vascular cells through a balance of pro‐ and anti‐angiogenic factors . It occurs through a sequence of procedures consisting of the recruitment of pericytes, stimulation of endothelial cells (ECs) by growth factors from the autocrine and paracrine systems, liberation of both the ECs and pericytes by degrading the ambient extracellular matrix (ECM), EC proliferation and migration, and their ultimate reorganization into a three‐dimensional tubular structure …”
Section: Introductionmentioning
confidence: 99%
“…It decreased after 14 days when the healing process had entered the hard callus and remodeling phase. 15,30,[58][59][60][61] Nakatsu et al reported that there was an association of VEGF with vascular morphometry, in which several VEGF isoforms such as VEGF121 and VEGF165 induce an increase in the diameter, number of branches, and total vascular length during angiogenesis in in vitro models. Apart from its role by increasing the vascular permeability, VEGF was also found to tend to increase the diameter of blood vessels through proliferation and increase in the number of endothelial cells (hyperplasia) in newly formed vascularization and not the result of enlargement of endothelial cells (hypertrophy).…”
Section: Discussionmentioning
confidence: 99%